2019
DOI: 10.3389/fnagi.2019.00177
|View full text |Cite
|
Sign up to set email alerts
|

The Precursor to Glutathione (GSH), γ-Glutamylcysteine (GGC), Can Ameliorate Oxidative Damage and Neuroinflammation Induced by Aβ40 Oligomers in Human Astrocytes

Abstract: Glutathione (GSH) is one of the most abundant thiol antioxidants in cells. Many chronic and age-related diseases are associated with a decline in cellular GSH levels or impairment in the catalytic activity of the GSH biosynthetic enzyme glutamate cysteine ligase (GCL). γ-glutamylcysteine (GGC), a precursor to glutathione (GSH), can replenish depleted GSH levels under oxidative stress conditions, by circumventing the regulation of GSH biosynthesis and providing the limiting substrate. Soluble amyloid-β (Aβ) oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 62 publications
1
32
0
2
Order By: Relevance
“…Moreover, inflammation is a principal contributor to ischemic injury. γ-GC exerts an anti-inflammatory effect on AD and sepsis [23,32]. Therefore, in a future study, we can further explore whether γ-GC has the capacity to combat inflammation and inhibit ferroptosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, inflammation is a principal contributor to ischemic injury. γ-GC exerts an anti-inflammatory effect on AD and sepsis [23,32]. Therefore, in a future study, we can further explore whether γ-GC has the capacity to combat inflammation and inhibit ferroptosis.…”
Section: Discussionmentioning
confidence: 97%
“…It was first confirmed in 1983 that γ-GC, an intermediate dipeptide with a sulfhydryl group in the GSH synthesis pathway, could increase the levels of GSH in the kidney [20]. Further studies have demonstrated that γ-GC and its esterified form GCEE can protect against oxidative damage in a variety of cell types through catalysis by GSS to produce intracellular GSH [23,24,31]. Recent studies have shown that compared with NAC and GSH supplementation, γ-GC administration was more effective in preventing lipopolysaccharide-(LPS-) or cecal ligation and puncture-(CLP-) induced systemic inflammatory responses [32].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite multiple clinical trials with current glutathione-based therapies, improved clinical outcomes in CF have not been achieved [6,7]. As a precursor to glutathione, GGC has been consistently shown to increase intracellular levels of glutathione in both in vivo and in vitro models [16][17][18][21][22][23][24], and to reduce inflammation and oxidative stress [19,43,44]. Recently, it was shown that GGC exhibits anti-inflammatory effects in an in vivo and in vitro mouse sepsis model [24].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione protects the brain from oxidative stress, xenobiotics, and neuroinflammation (Braidy et al, ) and studies show that glutathione shortages have a negative impact on brain health and neurodevelopment (Forman, Zhang, & Rinna, ). In addition, glutathione is also involved in preventing toxins and deleterious compounds from entering the brain as glutathione is an integral part of the choroid plexus, which forms the blood–cerebral spinal fluid barrier (Kratzer et al, ).…”
Section: Introductionmentioning
confidence: 99%